Development of Articulate Storyline 3-Based for Chemical Bonding Teaching Materials - Lestarani, Dewi; Tanone, Kalista L.K.; Parera, Lolita A.M.; Lalang, Arvinda C.; Naat, Johnson N. (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The development of Articulate Storyline 3 (AS3)-based chemistry teaching resources on chemical bonding is the aim of this research. the subject of research was 10th-grade senior high school students. This research was conducted to investigate the form of creation and viability of chemical bonding teaching materials using the AS3 application. Minor modifications are made to the Borg and Gall method for instructional design for the production of AS3-based chemical bonding teaching materials. The technique consists of five steps: preliminary studies, product design plan (planning and development), product validation (validation design and revision), field trials, and final product dissemination. The instruments used in this study were interview sheets, questionnaires in the form of instrument validation for material experts, and media experts, tests for students, and documentation. Material expert data, media, and student responses were obtained and analyzed to describe the validity and feasibility of teaching materials. The findings indicated that the optimal percentage was 96.42%, while the very excellent percentage was 96.66%. The results of the evaluation of the feasibility of teaching materials by material specialists and media specialists were 83.07% and 84.61 %, respectively, in the very excellent category. According to the findings of expert evaluations and field testing of chemical teaching materials based on AS3, this chemical bond material is very appropriate for use in educational settings.